To Regulate or Not to Regulate: Emotion Regulation in Participants With Low and High Impulsivity - Maier, Moritz Julian; Schiel, Julian Elias; Rosenbaum, David; Hautzinger, Martin; Fallgatter, Andreas Jochen; Ehlis, Ann-Christine (Frontiers in Behavioral Neuroscience, 2021)
Successful emotion regulation plays a key role in psychological health and wellbeing. In this study, we tested emotion regulation abilities and the impact of emotion regulation on a subsequent emotional Stroop task in participants with low vs. high impulsivity. A negative emotion inducing movie scene was presented with either the instruction to suppress or allow all upcoming feelings. This was followed by an emotional Stroop task. To assess the effects of emotion regulation, electromyography (EMG) over the Corrugator Supercilii was applied. Neurophysiological mechanisms were measured with functional near-infrared spectroscopy over frontal brain areas. While for the low impulsive group EMG activation was low independently of the instruction, highly-impulsive participants showed increased EMG activity if they were not explicitly instructed to suppress upcoming feelings. With the same extent of functional connectivity within frontal lobe networks, the low impulsive participants controlled their emotions better (less EMG activation) than the highly impulsive participants. In the Stroop task the low impulsive subjects performed significantly better, the emotion regulation condition had no significant influence on the results. We conclude that the cognitive control network is an essential requirement for emotion regulation. Persons with high cognitive control show implicit capabilities to regulate their emotions, persons with low cognitive control abilities need external instructions (= explicit emotion regulation) to achieve similar low expressions of emotionality.